Further insights into the role of methional and phenylacetaldehyde in lager beer flavor stability - Costa, M. Soares da (2011)
This work attempts to measure the importance of methional and phenylacetaldehyde on the flavor stability of beer, as direct participants or as indicators of aroma deterioration. A trained sensory panel identified the most important descriptors related to the typical aroma of aged beer: “malty”, “honeylike”, “cooked potato”, and “metallic”. By GC-olfactometry analysis, six aromatic zones related to the selected descriptors were highlighted, and by using GC-MS techniques it was possible to identify methional and phenylacetaldehyde as being responsible for two odor zones. The quantification of these molecules in samples submitted to forced aging treatments showed that the levels of methional and phenylacetaldehyde are dependent on the temperature of storage. Normal aged beers were also analyzed, and it was observed that these compounds accumulate with time of storage. Furthermore, these molecules were negatively correlated with the aroma quality of beer as evaluated by a sensorial panel. To validate the sensory impact of these substances, a fresh beer was spiked with these molecules and also with trans-2-nonenal, singly and in combination, and the similarity value between samples and the aged beer was then determined. The highest value from the similarity tests was 72% when the three compounds were added simultaneously. The combination of the two Strecker aldehydes increases by 54% the degree of similarity, indicating the key role played by these molecules in the aroma deterioration of beer. Finally, the kinetic parameters, Ea and k, were calculated, and it was observed that the Arrhenius equation described well the temperature dependence of the reaction rate constant. Measuring the concentration of methional and phenylacetaldehyde may provide information about the key steps along the process that most affect the flavor stability of beer, which may be useful in establishing the best storage conditions.